THE APPLICATION OF COMPUTER GRAPHICS AND MODERN CAD SYSTEMS IN ENGINEERING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides a comprehensive analysis of the application of computer graphics and modern Computer-Aided Design (CAD) systems in contemporary engineering. By synthesizing recent scientific literature, industry case studies, and expert interviews, the study explores how the convergence of digital visualization technologies and advanced modeling platforms has transformed engineering workflows across civil, mechanical, and aerospace disciplines. The research employs a mixed-methods approach, combining systematic literature review, comparative project analysis, and qualitative insights from leading practitioners. Results indicate significant improvements in design precision, efficiency, and stakeholder engagement attributed to the adoption of CAD and computer graphics, alongside persistent challenges such as interoperability, cybersecurity, and the need for ongoing professional development. The article concludes that computer graphics and CAD systems are foundational to the digital transformation of engineering, serving as catalysts for innovation, interdisciplinary collaboration, and sustainable development. Recommendations for future research include prioritizing artificial intelligence integration, standardization of file formats, and the modernization of engineering education curricula.